2009
DOI: 10.1017/s002202990800383x
|View full text |Cite
|
Sign up to set email alerts
|

Use of FTIR and mass spectrometry for characterization of glycated caseins

Abstract: This study investigates the potential of Fourier transform infrared spectroscopy (FTIR) to monitor glycation-induced changes in protein structure. Aqueous solutions of sodium caseinate and glucose (1:2 w/w, pH 6.7) were heated at 90 degrees C for 0, 10, 20, 40 and 60 min. Evidence for caseinate glycation was obtained by mass spectrometry techniques (electrospray (ESI) and matrix-assisted laser desorption ionisation (MALDI)). FTIR was able to discriminate between glycated and non-glycated sodium caseinate, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 12 publications
4
33
0
Order By: Relevance
“…According to Amiza et al [25] water holding capacity increased with an increased in degree of hydrolysis. Besides, at higher hydrolysis, polar groups such as COOH and NH 2 increased thus gave significant effects on water absorption and tend to exert better water-holding capacity [22]. In this study the functional group analysis showed that NH group peak was higher in angelwing hydrolysate compared to the flesh thus support the finding by Kristinsson and Rasco [28].…”
Section: Functional Group Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…According to Amiza et al [25] water holding capacity increased with an increased in degree of hydrolysis. Besides, at higher hydrolysis, polar groups such as COOH and NH 2 increased thus gave significant effects on water absorption and tend to exert better water-holding capacity [22]. In this study the functional group analysis showed that NH group peak was higher in angelwing hydrolysate compared to the flesh thus support the finding by Kristinsson and Rasco [28].…”
Section: Functional Group Analysissupporting
confidence: 80%
“…Therefore, this result is in accordance with the sensory analysis which showed that angelwing hydrolysate was bitter due to the presence of the high peak of N-H groups. Besides, Figure 2 showed angelwing hydrolysate has peak bands at 1640 cm -1 while the flesh has a peak bands at 1654 cm -1 which attributed to the carbonyl (C=0) stretch vibration centered approximately between 1650 cm -1 -1540 cm -1 [22]. These bands indicated the presence of functional compounds strong amide I and II in protein amide group (-CONH 2 ) which this amides of carboxylic acid (RCONH 2 ) were bitter [23].…”
Section: Functional Group Analysismentioning
confidence: 99%
“…The most distinctive spectral features for hydroxyl groups were the bands in the regions of 3700–3200 cm −1 and 1100–1000 cm −1 denoting hydroxyl and CO stretching vibration, respectively. Figure shows the FT‐IR spectrum of RDG and conjugate incubation at 60 °C for 24 h. RDG showed all the normal features of a protein spectrum, with strong amide I and amide II features between 1700 and 1500 cm −1 and was identical to findings with amide I and II of sodium caseinate form centered at 1660 and 1530 cm −1 . The absorption band at 3296 cm −1 arises from hydrogen bonding between protein chains and moisture in the protein.…”
Section: Resultsmentioning
confidence: 81%
“…Fourier‐transform infrared (FTIR) spectroscopy was used to differentiate between glycated and non‐glycated SCN and to provide complementary information about changes in the protein structure of glycated samples.…”
Section: Methods Used To Monitor Glycationmentioning
confidence: 99%
“…Mass spectrometry (MS) techniques are now used for routine analysis and quantification of the degree of glycation in complex protein mixtures . Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) gave evidence for the glycation of SCN with up to four glucose units depending on the heating time …”
Section: Methods Used To Monitor Glycationmentioning
confidence: 99%